1957
DOI: 10.1084/jem.106.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Long Chain Formation by Strains of Group a Streptococci in the Presence of Homologous Antiserum: A Type-Specific Reaction

Abstract: In the course of studies of the bactericidal system for the detection of typespecific antibody to group A streptococci (1), a number of strains were found which grew in extremely long chains in the presence of homologous antiserum. This paper reports some preliminary experiments designed to gain further insight into the mechanism of this phenomenon. The results indicate that long chain growth in liquid media of the strains of streptococci studied is dependent in part upon the interaction of type specific antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

1959
1959
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 7 publications
3
36
0
Order By: Relevance
“…Although this relation is presently under investigation, the results showing unregulated cell division with multiple septa in different planes in M1⌬CdhA and restoration of these defects in M1⌬CdhA::cdhA clearly indicated that the cdhA is a cell division plane recognition protein playing a crucial role in early events of cell division and ultimately chain formation in S. pyogene. Several decades ago, the induction of long chains in GAS was attributed to the presence of type M-specific antibody (53). However, the molecular and genetic basis of bacterial chain formation in GAS that is described in this study is distinct from the trypsin-sensitive, and type-specific antibody-mediated physical associations of more than one bacterial chain (53).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Although this relation is presently under investigation, the results showing unregulated cell division with multiple septa in different planes in M1⌬CdhA and restoration of these defects in M1⌬CdhA::cdhA clearly indicated that the cdhA is a cell division plane recognition protein playing a crucial role in early events of cell division and ultimately chain formation in S. pyogene. Several decades ago, the induction of long chains in GAS was attributed to the presence of type M-specific antibody (53). However, the molecular and genetic basis of bacterial chain formation in GAS that is described in this study is distinct from the trypsin-sensitive, and type-specific antibody-mediated physical associations of more than one bacterial chain (53).…”
Section: Discussionmentioning
confidence: 58%
“…Several decades ago, the induction of long chains in GAS was attributed to the presence of type M-specific antibody (53). However, the molecular and genetic basis of bacterial chain formation in GAS that is described in this study is distinct from the trypsin-sensitive, and type-specific antibody-mediated physical associations of more than one bacterial chain (53).…”
Section: Discussionmentioning
confidence: 58%
“…In one of these long chains were formed and in the other the cocci were mostly in pairs or very short chains. Bordet showed in 1897 (7) that streptococci grew in long chains in the presence of homologous antiserum, and Stollerman and Eckstedt (8) have recently related this phenomenon to the M-anti-M system. It was suspected that dissociation had occurred in the strain.…”
Section: Conversion Of Mucoid and Matt To Glossy Colony Forms By Hyalmentioning
confidence: 99%
“…Type specific antibody titer was determined by two methods used routinely in this laboratory-the bactericidal test modified slightly from that described by Lancefield (24), and the long chain test described by Stollerman and Ekstedt (25). A positive bactericidal test depended upon opsonization of the streptococci by immune serum and their subsequent phagocytosis by the normal control blood.…”
Section: Methodsmentioning
confidence: 99%